Life Cycle Assessment of Bioenergy Systems versus Fossil Fuel Alternatives: Insights for Sustainable Energy Transitions in Nigeria - Moses Adondua Abah; Micheal Abimbola Oladosu; Sunny Chukwuemeka Eke; Emmanuel Nwaka Nwaka; Ihechukwu Daniel Osuji; Abdulsalam Babaniya Muhammad; Joseph Osas Igbama; Clinton Arthur; Franklin Ogonna Ede; Olaide Ayokunmi Oladosu; Sunday Betini John; Bankole Emmanuel Aanu (Trends in Ecological and Indoor Environmental Engineering)
Background: The pressing necessity to address climate change has positioned energy decarbonization at the forefront of global sustainability initiatives. Decarbonization entails diminishing carbon intensity throughout the energy value chain by transitioning from fossil fuels to low- or zero-carbon alternatives, including renewable energy, green hydrogen, and bioenergy. Nigeria, despite its abundant fossil fuel resources, experiences persistent energy instability marked by inconsistent electricity delivery, low access rates, and excessive reliance on petroleum goods. The incorporation of renewable energy sources, including solar, wind, biomass, and small hydropower, has become an essential strategy for attaining energy security, sustainability, and climate resilience. Investing in renewable energy diminishes reliance on fossil fuels while fostering job development, energy fairness, and environmental conservation.